Efficacy and Safety of Raltegravir-Based Dual Therapy in AIDS Patients: A Meta-Analysis of Randomized Controlled Trials - Yinqiu Huang; Yinqiu Huang; Xiaojie Huang; Hui Chen; Hao Wu; Yaokai Chen; Yaokai Chen (Frontiers Media S.A., 2019)
Background: The life expectancy for HIV-infected individuals has improved dramatically because of improvements in antiretroviral therapy (ART). Today, a simplified two-drug regimen enhances adherence and treatment satisfaction by reducing adverse effects. Therefore, we need more evidence to show the benefits and risks of simplified ART regimens from randomized controlled trials (RCTs). We compared the efficacy and safety of raltegravir-based simplified dual therapy (DT) and of traditional triple therapy (TT) for people living with HIV/AIDS (PLWHA).Methods: We carried out a systematic review of RCTs. After using a combination of the key words "HIV," "raltegravir," and "protease inhibitor" to search the English-language electronic databases from January 1, 2004, to September 11, 2019, we pooled data across eligible studies and estimated the summary effect sizes with Review Manager (version 5.3).Results: We included eight RCTs involving 4420 PLWHA: 2187 (49.5%) received raltegravir-based simplified DT, and 2144 (48.5%) received traditional TT. The proportion of viral suppression was 79% at 48 weeks and 74% at 96 weeks in the simplified regimen, and the proportion of viral suppression was 78% at 48 weeks and 71% at 96 weeks in the traditional TT group. Furthermore, the proportion of viral suppression in the simplified DT group was greater than that in the TT group at 24 weeks (risk ratio 1.11, 95% confidence interval 1.02-1.21; p = 0.01). The CD4 cell counts in the simplified DT group were significantly higher at 48 weeks and 96 weeks than those in the group that received the traditional TT. Regarding adverse events and mortality rates, the DT and TT groups were similar. However, there was better adherence in the DT group than in the TT group.Conclusion: We found that the simplified regimen was noninferior to TT regimen in regard to viral suppression. Furthermore, the simplified DT regimen had a better CD4 cell count and lower adverse events than the TT regimen.